Problem Penerapan Standar Pelayanan Publik Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Sidoarjo - Munawaroh, Richul (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
One of the crucial services that often still encounters shortcomings in the fulfillment of public services to the community is the Capital Investment Services And One Door Integrated Service (DPMPTSP) of Sidoarjo Regency. Complaints were also submitted by DPMPTSP applicants for Sidoarjo Regency regarding poor service, overlapping information, and inappropriate service completion periods. The purpose of this study is to determine the Public Service Standards at the Capital Investment Services And One Door Integrated Service of Sidoarjo Regency. In this study, researchers used qualitative methods with a case study approach. In research using data collection techniques in the form of interviews, observations, documentation and literature studies. Data analysis is carried out through several stages, namely data collection, data condentation, data display and data conclusion drawing/verification. The results obtained from this study show that the implementation of public service standards based on aspects of employee consciousness, the existence of rules, organizational factors, ability and skill factors, as well as service facilities factors in the Capital Investment Services And One Door Integrated Service of Sidoarjo Regency is still not good. There is a need for work improvement and evaluation so that the competence of officers in providing services based on knowledge, expertise, skills, attitudes, and behaviors is even better to increase employee responsiveness to the public service standards that have been set.